Medial sustainable nail versus proximal femoral nail antirotation in treating AO/OTA 31-A2.3 fractures: Finite element analysis and biomechanical evaluation. Issue 3 (March 2019) - Li, Jiantao; Han, Lin; Zhang, Hao; Zhao, Zhe; Su, Xiuyun; Zhou, Jianfeng; Li, Chen; Yin, Peng; Hao, Ming; Wang, Kun; Xu, Gaoxiang; Zhang, Lihai; et al.
Highlights: Individual customization and rapid prototyping technology were used to establish fracture lines. The CT data was selected to detect tiny changes in the study. The medial sustainable nail construct might exhibit better biomechanical performance when compared with PFNA. The medial sustainable nail may be effective and feasible for unstable intertrochanteric fractures. Abstract: Objectives: Using finite element analysis and biomechanical tests, the biomechanical behaviors of Medial Sustainable Nail (MSN) and Proximal Femoral Nail Antirotation (PFNA) were compared for the fixation of fracture type of AO/OTA 31-A2.3. Methods: Finite element software Abaqus 6.14 was used to conduct axial loading of 2100 N and we analyzed the von Mises stress distribution and the model displacement of two implant models. Biomechanical tests were separately conducted in the axial stiffness test and axial cyclical loading test on a mechanical testing machine. Results: The results indicate that von Mises stress of MSN was lower than that of PFNA, and the model displacement in the MSN group was lower than that in the PFNA group. In the axial stiffness tests, MSN group was stiffer than PFNA construct. With respect to the axial load to ultimate failure, the PFNA construct exhibited higher loads exceeding 4000 N while the MSN construct withstood 3313.8 ± 92.8 N. Specifically, F10mm was 2178.6 ± 133.2 N of the MSN group and 1822.6 ± 93.1 N of the PFNA group (P = 0.001). Additionally, X2100N was 9.8 ± 0.5 mm of the MSN group and 11.7 ± 0.7 mm of the PFNA group (P = 0.002). The MSN group exhibited superior performances in terms of the mean value of the vertical displacement, frontal rotation angle, and lateral rotation angle. Conclusions: The results indicated that the MSN construct might exhibit a better biomechanical performance when compared with that of the PFNA in reducing displacement and anti-varus in fracture type of AO/OTA 31-A2.3.